Modelo de gestión social para la cooperativa de ahorro y crédito Cámara de Comercio del cantón Bolívar LTDA - Almeida Pérez, María de los Ángeles (2019)
This titling work was based on the proposal of a model for the management of socially responsible actions in the Savings and Credit Cooperative Chamber of Commerce of Cantón Bolívar Ltda., For this purpose three phases were established, where the interview was applied to the executives of the Cooperative, in order to know the current situation of the same regarding the management of the social activities that are carried out in the institution; through a bibliographic review and a comparative analysis between social models and cooperative balances, the structure with the components of the social management model was proposed in which the type of institution that is the Cooperative to study was taken into account; The stages of the social management model were distributed in relation to the cycle of continuous improvement such as the P, H, V, A, as well as the guidelines of each stage of the proposed model in order to manage the execution of the social activities of the Cooperative. The proposed model was based on the systematic and process approach, the first that allowed to have a general perspective, determining that all the components work in a whole; The second approach shows that the model has inputs that enter the process such as the needs of interest groups, information, resources, and outputs that will be obtained after the management of social activities such as support for community social management , and social inclusion. Finally, the consultation of experts to professionals with knowledge about the subject was used to validate the proposed model.